Ontogenetic shift in the diet of Dajaus monticola (Mugiliformes: Mugilidae) with comments in the recruitment of young individuals in the Honduran Caribbean coast. Issue 1 (1st January 2021) - Matamoros, Wilfredo A.; Fenoglio, Stefano; Clark, Scott R.; Schaefer, Jacob F.
ABSTRACT: Studies have been devoted to describing the diet of D. monticola . However, knowledge of how D. monticola utilizes food resources through ontogeny remains unknown. We characterized D. monticola general dietary patterns and tested for ontogenetic diet shifts. We also inferred on juvenile recruitment patterns. We examined the stomach contents of 120 specimens ranging in size from 20 to 154 mm in standard length (SL). To infer on recruitment periodicity, we examined the size of specimens deposited in museum collections to compile size frequencies by month. We assume that the occurrence of smaller-size class categories will shed light on their recruitment time. Our results show that D. monticola is an omnivore that largely feeds on aquatic insects but also includes detritus, terrestrial material, fishes and crustaceans. Our analysis did not detect strong changes in diet through ontogeny, instead some changes were detected but mainly on the percentage of some food items included at different size category classes. In regards to the recruitment periodicity, we found younger D. monticola (20–40 mm SL) throughout most of the year, suggesting that they may be reproducing for longer periods of time than those previously reported from Honduras.